Intra‐articular osteoid osteoma of the capitulum: A diagnostic challenge. Issue 5 (20th May 2022) - Shariatzadeh, Hooman; Bahrabadi, Mehrdad; Amiri, Shayan; Jahanshahi, Fatemeh; Joudi, Samad; Bahrabadi, Marjan
Abstract: Here, we describe the first case of intra‐articular osteoid osteoma of the capitulum, which is presented as elbow pain, extension lack, and sensation of click in joint flexion. Surgical treatment either arthroscopic or open is more in use in this location of the tumor than cortical osteoid osteoma. Abstract : We describe the first case of intra‐articular osteoid osteoma of the capitulum presented as elbow pain, extension lack, and sensation of click in joint flexion. Surgical treatment either arthroscopic or open is more in use in tumor location than cortical osteoid osteoma. Radiofrequency ablation should be used with extreme caution.